SOSIALISASI PENYUSUNAN LAPORAN KEUANGAN KOPERASI MENGGUNAKAN APLIKASI MICROSOFT EXCEL DI KPRI PATUT PATUH PATJU KABUPATEN LOMBOK BARAT - I Gusti Ayu Oka Netrawati; I Gusti Agung Didit Eka Permadi; Faezal Faezal (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
A cooperative is a business entity composed of individuals or legal entities based on cooperative principles and serves as a people's economic movement grounded in cooperation. The Employees' Cooperative of the Republic of Indonesia (KPRI) Patut Patuh Patju in West Lombok Regency does not have a Microsoft Excel template application for preparing its financial reports. The conclusion drawn from this community service activity is that through socialization and assistance, it is expected that the cooperative administrators at KPRI Patut Patuh Patju in West Lombok Regency will be able to prepare profit-sharing (SHU) reports and balance sheets using the Microsoft Excel cooperative application. This will enable them to provide accountability to cooperative members during the Annual Members Meeting (RAT) and to obtain funding from external parties, especially banks, which will ultimately increase the cooperative’s capital. The recommendation provided by the community service team to the administrators managing the cooperative at KPRI Patut Patuh Patju is that, considering the limited number of participants who had the opportunity to take part in the socialization, assistance activities, and acknowledging that it is not an easy task that there is a need for ongoing mentoring efforts and continuous guidance to achieve optimal results.